Lao PDR Economic Monitor, December 2017 : Lowering Risks and Reviving Growth - World Bank Group (World Bank, Washington, DC, 2017)
The Lao PDR Economic Monitor provides updates on macroeconomic developments and sectoral issues in the country. It is produced bi-annually and distributed widely to the government agencies, development partners, the private sector, think tanks, civil society organizations, and academia. Addressing macroeconomic risks remains a pressing priority while improving environment for long-term growth is a continuous agenda. To create a more stable macroeconomic environment for reforms, maintaining fiscal discipline and bolder steps towards fiscal consolidation is of utmost importance at this stage. Growth is projected to further moderate to 6.7 percent in 2017, below historical averages, but towards a more sustainable level. Continued expansion in power generation, manufacturing, and agriculture are weighed down by slight deceleration in investment, moderating credit growth, stronger controls over government spending and lower-than-expected tourism performance. Domestic demand also shows signs of slowing. Still, compared to developing East Asia and Pacific (EAP) and regional peers such as Cambodia, Thailand and Vietnam, growth remains robust. Headline inflation further declined in 2017, reflecting falling food prices and slowing aggregate demand, amidst a gradual recovery in oil prices. In this regard, the proposed 2018 best, only a modest adjustment. More meaningful consolidation will require stronger efforts to strengthening revenue collection through improved tax administration, fiscal consolidation is of utmost importance at this stage.